Galectin‐1 Triggers Epithelial‐Mesenchymal Transition in Human Hepatocellular Carcinoma Cells. Issue 6 (June 2015) - Bacigalupo, María L.; Manzi, Malena; Espelt, María V.; Gentilini, Lucas D.; Compagno, Daniel; Laderach, Diego J.; Wolfenstein‐Todel, Carlota; Rabinovich, Gabriel A.; Troncoso, María F.
<x xml:space="preserve">Abstract</x> Galectin‐1 (Gal1), a β‐galactoside‐binding protein abundantly expressed in tumor microenvironments, is associated with the development of metastasis in hepatocellular carcinomas (HCC). However, the precise roles of Gal1 in HCC cell invasiveness and dissemination are uncertain. Here, we investigated whether Gal1 mediate epithelial‐mesenchymal transition (EMT) in HCC cells, a key process during cancer progression. We used the well‐differentiated and low invasive HepG2 cells and performed 'gain‐of‐function' and 'loss‐function' experiments by transfecting cells with Gal1 cDNA constructs or by siRNA strategies, respectively. Epithelial and mesenchymal markers expression, changes in apico‐basal polarity, independent‐anchorage growth, and activation of specific signaling pathways were studied using Western blot, fluorescence microscopy, soft‐agar assays, and FOP/TOP flash reporter system. Gal1 up‐regulation in HepG2 cells induced down‐regulation of the adherens junction protein E‐cadherin and increased expression of the transcription factor Snail, one of the main inducers of EMT in HCC. Enhanced Gal1 expression facilitated the transition from epithelial cell morphology towards a fibroblastoid phenotype and favored up‐regulation of the mesenchymal marker vimentin in HCC cells. Cells overexpressing Gal1 showed enhanced anchorage‐independent growth and loss of apico‐basal polarity. Remarkably, Gal1 promoted Akt activation, β‐catenin nuclear translocation, TCF4/LEF1 transcriptional activity and increased cyclin D1 and c‐Myc expression, suggesting activation of the Wnt pathway. Furthermore, Gal1 overexpression induced E‐cadherin downregulation through a PI3K/Akt‐dependent mechanism. Our results provide the first evidence of a role of Gal1 as an inducer of EMT in HCC cells, with critical implications in HCC metastasis. J. Cell. Physiol. 230: 1298–1309, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company